Slc6a20a Heterozygous and Homozygous Mutant Mice Display Differential Behavioral and Transcriptomic Changes - Kim, Junhyung; Roh, Junyeop Daniel; Kim, Seongbin; Kang, Hyojin; Bae, Mihyun; Kim, Eunjoon (Frontiers in Molecular Neuroscience, 2022)
SLC6A20A is a proline and glycine transporter known to regulate glycine homeostasis and NMDA receptor (NMDAR) function in the brain. A previous study found increases in ambient glycine levels and NMDA receptor-mediated synaptic transmission in the brains of Slc6a20a-haploinsufficient mice, but it remained unknown whether Slc6a20a deficiency leads to disease-related behavioral deficits in mice. Here, we report that Slc6a20a heterozygous and homozygous mutant mice display differential behavioral phenotypes in locomotor, repetitive behavioral, and spatial and fear memory domains. In addition, these mice show differential transcriptomic changes in synapse, ribosome, mitochondria, autism, epilepsy, and neuron-related genes. These results suggest that heterozygous and homozygous Slc6a20a deletions in mice lead to differential changes in behaviors and transcriptomes.